Estudo de técnicas não destrutivas na recuperação de marcações adulteradas em chapas metálicas - Lima, Mariana Gaudencio Barbosa. (2018)
This work aims the evaluation of non-destructive techniques known as eddy current (EC)/ magnetography (MG)/ magneto-optical imaging (MOI) and magnetic particle (MP) in the forensic restoration of obliterated marks. The samples used in this study were extracted from two different vehicle’s chassis. Since the materials of the chassis are unknown the microstructural, chemical and magnetic characterizations were needed. In addition, the samples were identified with alphabetic codes, impressed by stamping and engraving. After the identification, the samples suffered two types of adulteration: removal of the code and re-stamping. The performance of the two non-destructive methods was evaluated in comparison with the destructive method of restoration by chemical etching, current used by the Brazilian investigators, considering: time of analysis, imaging and detection, sensibility, applicability, safety, mobility and cost. Considering the results obtained, the EC/MG/MOI and MP restoration’s methods presented a good performance on the recovery of the original stamped codes, obliterated by removal and re-stamping.